2018
DOI: 10.1088/1748-9326/aae3b1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the forest definitions adopted by African countries on carbon conservation

Abstract: In this paper, we aim to assess the impacts of the forest definitions adopted by each African country involved in the global climate change programmes of the United Nations on national carbon emission estimations. To do so, we estimate the proportion of national carbon stocks and tree cover loss that are found in areas considered to be non-forest areas. These non-forest areas are defined with respect to a threshold on the percentage of tree cover adopted by each country. Using percent tree cover and abovegroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The discrepancy can be explained in terms of the different definitions of forest used in CCI when generating land cover maps and in the FRA when using national data of different quality to generate the country estimates. However, the estimate of forest area obtained 635 in this study is likely to be an underestimate, since it excluded land cover classes with a sparse tree and vegetation component that could be attributed to forest under less restrictive definitions of percentage tree cover (Mermoz et al, 2018).…”
mentioning
confidence: 88%
“…The discrepancy can be explained in terms of the different definitions of forest used in CCI when generating land cover maps and in the FRA when using national data of different quality to generate the country estimates. However, the estimate of forest area obtained 635 in this study is likely to be an underestimate, since it excluded land cover classes with a sparse tree and vegetation component that could be attributed to forest under less restrictive definitions of percentage tree cover (Mermoz et al, 2018).…”
mentioning
confidence: 88%
“…Indeed, in terms of species richness, forbs dominate grasslands worldwide, and are often the most species-rich functional group, for example in North American prairie, African savannah, Mongolian steppes, and South American pampas, campos and cerrados 21 . According to some definitions, grasslands can also have a relatively high tree cover before they become classed as forest 22 . Natural grasslands are often grazed by wild herbivores, including many large mammals, but large areas are also used for domestic livestock.…”
Section: Defining Grasslandsmentioning
confidence: 99%
“…Our analysis has also shown that the extent of HCVF, HCSF and tropical peatland forests is contingent on the choice of forest map, resulting in a range from 11 to 40 million km 2 according to the criteria specified in figure 2. This finding adds to a growing body of literature showing that the definition of forest significantly impacts estimates of forest cover and forest cover change (Chazdon et al 2016, Sexton et al 2016, Mermoz et al 2018. The lack of a well-agreed forest definition led nine environmental and social NGOs to launch the Accountability Framework initiative in 2016; a framework that has been developed to provide companies with detailed guidance to implement their commitments and standardize definitions of forest, deforestation, and related terms (Weber and Partzsch 2018).…”
Section: Discussionmentioning
confidence: 85%